Assessment of Elastic Fibers in Tumor Stroma as a New Method to Predict 6-Year Outcomes for Gastric Cancer Patients - Xue, Xiaowei; Li, Yuan; Zhang, Yuhan; Wang, Pengyan; Li, Xiaoqing; Wei, Hongtao; Zhou, Weixun (Frontiers in Oncology, 2020)
Purpose: This study aimed to determine whether detecting elastic fibers in tumor stroma (EFTS) could be used as a new method for predicting the prognosis of gastric cancer (GC) patients. Materials and Methods: EFTS expression was determined by histochemistry in 160 gastric cancer patients who underwent gastrectomy. Based on the staining results, the patients were divided into three groups according to their EFTS expression level: low (n=57), moderate (n=50) and high (n=53). The clinicopathological data and 6-year survival data were analyzed among different EFTS groups. Results: The expression of EFTS was closely related to lymphovascular invasion (P=0.010), blood transfusion in operation (P＜0.001), recurrence rate (P＜0.001) and motility (P＜0.001). High expression of EFTS was also correlated with recurrence-free survival (RFS) and overall survival (OS) in gastric cancer patients by Kaplan–Meier curve (P＜0.001 for RFS and P＜0.001 for OS, respectively). Conclusions: Multivariate analysis showed EFTS was an independent prognostic factor for RFS and OS. In conclusion, detecting EFTS to predict the prognosis of gastric cancer patients is effective and highly feasible.